The Histone Deacetylase 9 Stroke-Risk Variant Promotes Apoptosis and Inflammation in a Human iPSC-Derived Smooth Muscle Cells Model - Granata, Alessandra; Kasioulis, Ioannis; Serrano, Felipe; Cooper, James D.; Traylor, Matthew; Sinha, Sanjay; Markus, Hugh S. (Frontiers in Cardiovascular Medicine, 2022)
A common variant in the Histone Deacetylase 9 (HDAC9) gene is the strongest genetic risk for large-vessel stroke, and HDAC9 offers a novel target for therapeutic modulation. However, the mechanisms linking the HDAC9 variant with increased stroke risk is still unclear due to the lack of relevant models to study the underlying molecular mechanisms. We generated vascular smooth muscle cells using human induced pluripotent stem cells with the HDAC9 stroke risk variant to assess HDAC9-mediated phenotypic changes in a relevant cells model and test the efficacy of HDAC inhibitors for potential therapeutic strategies. Our human induced pluripotent stem cells derived vascular model shows enhanced HDAC9 expression and allows us to assess HDAC9-mediated effects on promoting smooth muscle cells dysfunction, including proliferation, migration, apoptosis and response to inflammation. These phenotypes could be reverted by treatment with HDAC inhibitors, including sodium valproate and small molecules inhibitors. By demonstrating the relevance of the model and the efficacy of HDAC inhibitors, our model provides a robust phenotypic screening platform, which could be applied to other stroke-associated genetic variants.